Development toxicity and cardiotoxicity in zebrafish from exposure to iprodione. (January 2021) - Wei, You; Meng, Yunlong; Huang, Yong; Liu, Zehui; Zhong, Keyuan; Ma, Jinze; Zhang, Weixin; Li, Yibao; Lu, Huiqiang
Abstract: Iprodione is a highly effective broad-spectrum fungicide commonly used for early disease control in fruit trees and vegetables. Pesticides often flow into watercourses due to rainfall, causing toxicity in non-target organisms, eventually entering the food chain. However, little information is available in the current literature about the toxicity of iprodione to cardiac development. The present study aimed to investigate the effect of iprodione on early embryonic development and its cardiotoxicity in aquatic animals, using zebrafish as a model. At 6–72 h post-fertilization (hpf), zebrafish were exposed to concentrations of 15 mg/L, 20 mg/L, and 25 mg/L (72 h-LC50  = 21.15 mg/L). We found that exposure to iprodione resulted in yolk edema, increased mortality, and shortened body length in zebrafish embryos. In addition, iprodione was also found to induce edema in the pericardium of zebrafish, decrease heart rate, and cause the failure of cardiac cyclization. Exposure to iprodione significantly increased the accumulation of ROS and altered the activity of antioxidant enzymes (MDA, CAT) in zebrafish embryos. Moreover, iprodione induced changes in the transcription levels of heart developmental-related genes and apoptosis-related genes. In addition, Astaxanthin (antioxidant) can partially rescue the toxic phenotype caused by iprodione. Apoptosis-related genes and heart developmental-related genes were rescued after astaxanazin treatment. The results suggest that iprodione induces developmental and cardiac toxicity in zebrafish embryos, which provides new evidence of the toxicity of iprodione to organisms in aquatic ecosystems and assessing human health risks. Graphical abstract: Image 1 Highlights: Iprodione increased mortality, shortened body length, induced yolk sac edema. Iprodione induced pericardium edema, affect heart rate and cardiac loop. Exposure to iprodione induced oxidative stress in zebrafish embryos. Iprodione induced changes in the transcription levels of heart development genes. Iprodione induced alterations in transcription levels of apoptosis related genes.